Kebijakan Negara Filipina Tentang Penembakan Mati Pelaku Kejahatan Narkoba Dalam Perspektif Hukum Hak Asasi Manusia Internasional - Brenda Jacobs; Lucia Charlota Octovina Tahamata; Dyah Ridhul Airin Daties (Faculty of Law, Universitas Pattimura, 2021)
Introduction: The Philippines is one country that provides serious penalties for drug offenders. The war on drugs is a policy carried out by the president of the Philippines, Duterte, to eradicate drug crimes. The victims who are suspected drug users and dealers are arrested and shot to death without a judicial process and a decision that has permanent legal force. Purposes of the Research: The method used is a normative juridical research method using a case approach, a statutory approach and a conceptual approach.Methods of the Research: This research is an empirical legal research, using a law approach and a case approach. Research data sources include primary, secondary and tertiary data sources. Data collection techniques in the form of library research and field studies. Technical Analysis of the data used is descriptive qualitative.Results of the Research: The results obtained explain that the regulation of drug dealers and users is regulated in international law and is also regulated in Philippine national law. The war against drugs in the Philippines by shooting dead drug crimes is contrary to international legal instruments, namely violations of human rights, especially the right to life. Because someone can not be killed arbitrarily, and can not be punished before the court site for accusations of wrongdoing. Thus, it is hoped that the policies carried out by the President of the Philippines will prioritize human rights with more attention to the rules regarding human rights.